PERAN GURU BESERTA ORANG TUA DALAM MENGATASI KESULITAN MEMBACA SISWA TERHADAP PROSES PEMBELAJARAN DI SEKOLAH DASAR - Imam, Nurul; Sedya Santosa; Nisa Syuhda; Muhammad Nizar Al Bashir; Asnafiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the role of teachers and parents in overcoming students' reading difficulties during the learning process in elementary schools. The method used in this research is Systematic Literature Review (SLR), with data sources coming from articles that have been published through the Online Journal System (OJS). A total of 10 relevant articles obtained through a search using Google were documented and tabulated based on the similarity of findings or conclusions from each article. After the tabulation process, the data is analyzed, reduced, and then compiled into conclusions. The results of this research provide an overview of the role of teachers and parents in supporting students to overcome reading difficulties during the learning process in elementary school. Based on these findings, it is hoped that educators, especially teachers, can continue to increase synergy with parents in supporting students' literacy development, as well as, if relevant, integrating Islamic values ​​into the learning process.